2008
DOI: 10.1021/es800353f
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Sources of Perfluorinated Surfactants in Rivers in Japan

Abstract: We analyzed perfluorinated surfactants (PFSs) in 20 river samples and 5 wastewater secondary effluent samples in Japan to reveal their occurrence and sources. Nine PFS species were determined: perfluorooctanesulfonate (PFOS), perfluorooctane sulfonamide (FOSA), perfluoroheptanoate (PFHpA), perfluorooctanoate (PFOA), perfluorononanoate (PFNA), perfluorodecanoate (PFDA), perfluoroundecanoate (PFUA), perfluorododecanoate (PFDDA), and perfluorotridecanoate (PFTDA). PFSs were detected in all rivers, revealing natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 31 publications
5
112
3
Order By: Relevance
“…Some previous studies have also reported the occurrence of PFASs, especially PFOA and PFOS in river water globally (Hansen et al, 2002;Mclachlan et al, 2007;Murakami et al, 2008;Yeung et al, 2009;Nakayama et al, 2010;Hong et al, 2013;Wang et al, 2013;Zhang et al, 2013). In general, the PFAS concentrations in the Yangtze River were lower than those in other rivers in the world.…”
Section: Concentrations and Composition Of Pfass In Surface Watermentioning
confidence: 84%
“…Some previous studies have also reported the occurrence of PFASs, especially PFOA and PFOS in river water globally (Hansen et al, 2002;Mclachlan et al, 2007;Murakami et al, 2008;Yeung et al, 2009;Nakayama et al, 2010;Hong et al, 2013;Wang et al, 2013;Zhang et al, 2013). In general, the PFAS concentrations in the Yangtze River were lower than those in other rivers in the world.…”
Section: Concentrations and Composition Of Pfass In Surface Watermentioning
confidence: 84%
“…22 We also detected high levels of PFPeA, PFHxA, PFHpA, and PFHxS in water at these sites, with mean values of 74.5 (26.4−254) ng/L, 120 (27.8−462) ng/L, 127 (23.8−478) ng/L, and 488 (286−578) ng/L, respectively, which were much higher than those in water samples from WWTPs and lakes in previous studies. 5,23 In Labadie's study, adsorption in the filtration process of water samples is observed both in nylon and glass fiber filters. Using glass fiber filters, the sorption ranges from 10% to 30% for longchain PFCAs (CF 2 > 10), while the sorption of PFOS and PFBS is lower than 6%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar methods were applied by Kim (2012) to estimate the watershed-based riverine discharge load of PFOS on the Korean peninsula. Total flux of sewage-derived PFOS from Japan was estimated by use of per capita emission factor, which was derived from PFOS loads in the wastewater effluents and the population served by the WWTPs (Murakami et al, 2008). In China, discharges of PFOS from major rivers, effluent and sludge in several WWTPs were estimated by Chen et al (2011b).…”
Section: Potential Sources and Emission Estimationmentioning
confidence: 99%